(untitled) (Marketing Journal, 2025)
The article analyzes the importance, types and application of rational appeal elements in television advertising with examples. Rational appeals are classified based on comparative, one-sided and two-sided messages, and their effectiveness in promoting brands is considered. The study analyzes the advertising strategies of such well-known brands as BMW, Tide, Nestle, Oral-B, and also emphasizes the influence of advertising objectives, audience psychology and product characteristics on the selection of rational appeals.